Emergence of institutional antithrombotic protocols for coronavirus 2019 - Cohoon, Kevin P.; Mahé, Guillaume; Tafur, Alfonso J.; Spyropoulos, Alex C. (Research and practice in thrombosis and haemostasis, 2020)
INTRODUCTION The coronavirus disease 2019 (COVID‐19), first identified in December 2019 in Wuhan, China, is a major public health crisis with new infections increasing exponentially worldwide. 1 COVID‐19 is an acute infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV2) and has contributed to significant morbidity and mortality, including the development of coagulopathy. 2 Similar thrombotic and thromboembolic events have occurred during other viral outbreaks, including severe acute respiratory syndrome (SARS), Middle Eastern respiratory syndrome, and influenza A H1N1. 3–7 Venous thromboembolism (VTE) (ie, deep vein thrombosis or pulmonary embolism [PE]) is a common complication of acute infectious diseases, which increase VTE risk 2‐fold to 32‐fold. 8–10 Survival among patients with incident and recurrent VTE is significantly reduced, especially after PE. 11 Hospitalized patients with acute medical illness, including infections such as pneumonia, are at increased risk of VTE, both in‐hospital and for an extended period of time (up to 45 days) after hospital discharge. 8,9,12–16 Despite this well‐established association, 8–10 there are few data specifically addressing VTE in patients recently hospitalized with COVID‐19 infections. 17,18 Indeed, infection‐associated VTE might account for a substantial burden of incident or recurrent VTE among those with COVID‐19. 25,26 Common laboratory abnormalities include lymphopenia and increase in lactate dehydrogenase and inflammatory markers such as C‐reactive protein, D‐dimer, ferritin, interleukin (IL)‐6, and fibrinogen. 27,28 Thrombocytopenia 29 and increased D‐dimer levels 30 are the most consistent laboratory abnormalities associated with a higher risk of developing severe COVID‐19. [...]several protocols suggest measuring D‐dimers, prothrombin time, and platelet counts to help assess COVID‐19 severity. 41 Empiric evidence supports use of treatment dose unfractionated heparin (UFH) as improving thrombosis‐free survival in acute respiratory distress syndrome with influenza A H1N1 but not coronavirus. 42 There is also recent evidence that prophylactic doses of LMWH (namely, enoxaparin at 40‐60 mg subcutaneous [s.c.] daily) or UFH (10 000‐15 000 units/d) appears to be associated with better prognosis in COVID‐19 patients with serious illness meeting sepsis‐induced coagulopathy score of ≥4 or with markedly elevated D‐dimer (>6× ULN) compared to non–heparin users. 43 The World Health Organization interim guidance statement as well as a recent guidance statement from ISTH recommends prophylactic use of daily LMWH over twice‐daily subcutaneous UFH. 44,45 Obese patients with body mass index (BMI) >30 kg/m2 have increased risk of VTE, 46 recurrent VTE, 47 and postthrombotic syndrome 48; however, prior studies have mainly focused VTE prophylaxis on extreme obesity defined by BMI >40 kg/m2. In‐ and outpatients Inpatients In‐ and outpatients Outpatients In‐ and outpatients Inpatients and elderly in establishment ICU patients Thrombotic risk assessment Yes Yes Yes Yes Yes Not mentioned Not mentioned Criteria for VTE risk Use of Wells’ Criteria IMPROVE VTE score D‐dimer Use of ISTH DIC score IMPROVE VTE score D‐dimer Use of ISTH DIC score Immobilization > 48 h, cancer, recent surgery, personal history of VTE, BMI > 30 kg/m2, age > 70 y old Thrombotic risk and ISTH DIC score NA NA Hemostasis surveillance Not mentioned Not mentioned Yes Not mentioned Yes Yes Yes Assessment of bleeding risk Yes Yes Not mentioned Not mentioned Yes Yes Not mentioned Proposed prophylactic treatments Patients hospitalized with suspected or confirmed COVID‐19, VTE prophylaxis with enoxaparin at prophylactic or intermediate doses (ie, 40 mg s.c. daily or 40 mg s.c. twice daily, especially for BMI > 40 kg/m2) as the preferred agent over UFH, unless patients have acute renal failure or chronic kidney disease (CrCl < 15 mL/min); if CrCl < 15 mL/min, then UFH 5000 IU s.c. 3 times daily for BMI < 40 kg/m2 or 7500 IU s.c. twice daily for BMI